The Effect of Group Discussion to Improve the Students’ Writing Skills in Recount Text - Istiqomah, Dea Nurul; Lestari, Siti; Wahyuni, Sri (Dinamika Bahasa dan Budaya, 2025)
This study seeks to look into the impact of group discussions on the writing skills of grade X students, specifically focusing on recount texts at SMA Negeri 2 Kendal. This study aims to achieve the following objectives: (1) to gauge the writing skills of students regarding recount text when instruction is delivered without the incorporation of group discussion; (2) to evaluate the writing skills of students concerning recount text when instruction includes group discussion; and (3) to analyze the significant differences in students' writing skills on recount text between the two instructional approaches, namely without and with group discussion. This study relied on a quantitative technique and adopted a quasi-experimental design for its research probe. The data collection process involved the utilization of both pre-test and post-test equipment. The analysis of the data was conducted utilizing the IBM SPSS version 27. The analysis of the data indicated that students who engaged in group discussions demonstrated superior performance compared to those who did not participate in such discussions. The students participating in the experimental class achieved an average score of 56.97 on the pre-test, which increased to 73.46 on the post-test. This suggests that a significant disparity exists between students who received instruction that included group discussions and those who did not engage in such collaborative learning experiences. Keywords: Writing, Recount Text, Group Discussion.